Study of temperature and indium concentration-dependent dielectric constant and electron affinity effects on the exciton optical transition and binding energy in spherical GaSb–Ga1−xInxAsySb1−y–GaSb quantum dots (2010)
We have study the heavy-hole exciton states in GaSb–GaInAsSb–GaSb type-I spherical Quantum Dots, using temperature-dependent static dielectric constant and electron affinity, with a finite height potential barrier, as a function of the quantum dot radius for several values of Indium concentration. Our calculations have been worked out using interpolating methods to find the temperature and Indium concentration dependence of both the dielectric constant and electron affinity, in order to determine the conduction and valence band-offsets in GaSb–GaInAsSb–GaSb heterostructure by application of the Electron Affinity Rule. We have calculated the exciton binding energy and the corresponding transition energy from the exciton ground state to the heavy-hole level, using a variational procedure within the effective-mass approximation. We have found that the binding energy of the heavy-hole exciton presents changes due to the temperature dependence of the electron affinity and static dielectric constant. However, our results for the transition energy from the exciton ground state to the heavy-hole level coincide with those reported in a previous theoretical work, where we had found a very good agreement with photoluminescence and photoreflectance experimental studies at T=12 K in Ga1-xInxAsySb1-y films grown over GaSb substrates by liquid phase epitaxy